PERNIKAHAN BEDA AGAMA DALAM PERSPEKTIF AL-QUR’AN DAN SUNNAH SERTA PROBLEMATIKANYA - Zainul Mu’ien Husni (Universitas Nurul Jadid, 2018)
Social phenomena which proves many couples have got interfaith marriage in Indonesia and other countries. In this case, interfaith marriage is a marriage of a man of Muslim with non-Muslim women or otherwise, marriage the women of Muslim with male non-Muslim. Therefore, it is necessary for a comprehensive explanation about the law of interfaith marriage. Interfaith marriage in al-Quran and Sunnah can be classified into three, first, the marriage of men of Muslim with the polytheists (musyrikah) women, within the merriage of male of Muslim with polytheists women are disagreement about the law, Ibn Jarir al-Tabari permit the marriage of this category on condition that the polytheistic woman came from the non-Arabs nation’s which have a holy book or the bible, should be married by men of Muslim. Second, the marriage of men of Muslim with women Ahl al-Kitab (kitabiyyah). In this case the majority of ulama get argue that married to of kitabiyah women (Jewish and Christian faiths, either dhimmi or harbi) is permissible. And, third, the marriage of women of Muslim with a male of non-Muslim, whether the merriage to polytheistic or Ahl al-Kitab (kitabi) which in this case is based on the consensus among ulama of islamic jurisprudence (fiqh) that marriage with this category is haraam, whether the male non-Muslim kitabi classified or not.